2021
DOI: 10.1155/2021/9813773
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal lncRNA SCIRT/miR-665 Transferring Promotes Lung Cancer Cell Metastasis through the Inhibition of HEYL

Abstract: Lung cancer remains the leading cause of cancer-related death worldwide. Recently, extracellular vesicles such as exosomes have attracted considerable interest both as a source for theranostic biomarkers and an essential participant in lung cancer progression. However, how specific exosomal cargos, such as noncoding RNAs, are selectively packaged into exosomes and promote lung cancer progression remains unclear. In this study, we identified miR-665 as the most elevated exosomal miRNA from both non-small-cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
(40 reference statements)
0
19
0
Order By: Relevance
“…Notably, a recent study reported the upregulation of miR‐665 levels in lung cancer and metastatic disease samples. 26 Based on these findings, the regulatory mechanism of hsa_circ_0129047/miR‐665/ACVRL1 in the progression of LUAD should be investigated further in future studies. Our findings demonstrate that hsa_circ_0129047 serves as a tumor suppressor in LUAD as it strongly inhibits the tumorigenesis and malignancy of LUAD by modulating the miR‐375/ACVRL1 axis.…”
Section: Discussionmentioning
confidence: 94%
“…Notably, a recent study reported the upregulation of miR‐665 levels in lung cancer and metastatic disease samples. 26 Based on these findings, the regulatory mechanism of hsa_circ_0129047/miR‐665/ACVRL1 in the progression of LUAD should be investigated further in future studies. Our findings demonstrate that hsa_circ_0129047 serves as a tumor suppressor in LUAD as it strongly inhibits the tumorigenesis and malignancy of LUAD by modulating the miR‐375/ACVRL1 axis.…”
Section: Discussionmentioning
confidence: 94%
“…A large number of factors can be carried by EVs into NSCLC cells which play a role in NSCLC, including lncRNAs [ 16 , 43 , 44 ]. Following literature review and selection of related genes, we speculated that EVs may carry the following factors to exert an impact in NSCLC: lncRNA-LINC00662, lncRNA-TBILA, lncRNA-SNHG12, miR-744, and miR-378 [ 19 , 43 , 45–47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, EVs are known to possess the ability to carry lncRNAs into NSCLCs to modulate the progression of numerous malignancies [ 43 , 44 ]. One such lncRNA, namely lncRNA SNHG12, was previously found to be up-regulated in human osteosarcoma cells and NSCLC cells, along with the promotion of cell growth and proliferation [ 18 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are mainly transcribed by RNA polymerase II, typically by a 5′7-methylguanosine cap and a 3′ poly (A) tail. Similar to messenger RNAs, they are involved in the pathogenesis of cancer [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ]. Different classes of lncRNAs are generated from introns, exons, intergenic regions, telomerases, enhancers, or promoters [ 19 ].…”
Section: Long Non-coding Rnas and Potential Therapeutic Targeting In ...mentioning
confidence: 99%